2020
DOI: 10.1097/j.jcrs.0000000000000243
|View full text |Cite
|
Sign up to set email alerts
|

Trabecular microbypass stent implantation in pseudoexfoliative glaucoma: long-term results

Abstract: Purpose: To evaluate the long-term safety and efficacy of an iStent trabecular microbypass stent in combination with cataract surgery in pseudoexfoliative glaucoma (PXG). Setting: Private practice, Sioux Falls, South Dakota, USA. Design: Retrospective, consecutive case series. Methods: Eyes with a preoperative diagnosis of PXG implanted with a single iStent trabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…In addition, the proportion of eyes with IOP ≤15 mmHg nearly doubled versus preoperative (81% at 24 months versus 42% preoperatively). Consistent with prior studies evaluating IOP-lowering treatments, 10,[15][16][17]46,47 eyes with higher baseline IOP achieved a more robust postoperative IOP reduction than eyes with lower baseline IOP. Also consistent with prior MIGS studies, 16,17,48 our data suggested a slight diminution of IOP-and medication-reducing effects after the first year postoperative.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In addition, the proportion of eyes with IOP ≤15 mmHg nearly doubled versus preoperative (81% at 24 months versus 42% preoperatively). Consistent with prior studies evaluating IOP-lowering treatments, 10,[15][16][17]46,47 eyes with higher baseline IOP achieved a more robust postoperative IOP reduction than eyes with lower baseline IOP. Also consistent with prior MIGS studies, 16,17,48 our data suggested a slight diminution of IOP-and medication-reducing effects after the first year postoperative.…”
Section: Discussionsupporting
confidence: 82%
“…Consistent with prior studies evaluating IOP-lowering treatments, 10,[15][16][17]46,47 eyes with higher baseline IOP achieved a more robust postoperative IOP reduction than eyes with lower baseline IOP. Also consistent with prior MIGS studies, 16,17,48 our data suggested a slight diminution of IOP-and medication-reducing effects after the first year postoperative. This is not unexpected, as stent implantation was accompanied by phacoemulsification, which is known to have mild ocular hypotensive effects (generally under 2 mmHg) in medically controlled glaucomatous eyes, and that these effects typically begin to diminish after the first year postoperative.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…With up to 7 years of postoperative follow-up, iStent studies have often focused on patients with mild to moderate POAG undergoing cataract surgery, but an increasing number of studies have assessed iStent for different glaucoma types (eg, pseudoexfoliative, angle-closure, pigmentary), more advanced severity, standalone cases, and in combination with other procedures or stents. [11][12][13][14][15][16][17][18][19][20][21][22][23] The more recent iStent inject ® Trabecular Micro-Bypass (CE Mark 2010, FDA approval 2018) contains two stents that create two patent bypasses through the diseased trabecular meshwork. This device has been studied both with and without concomitant cataract extraction, and in studies with up to 5 years of follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…[40][41][42][43] In addition, several publications have shown this IOP association following iStent or iStent inject implantation. [15][16][17][18]26,27 Fewer studies have evaluated the relationship between preoperative medication burden and postoperative IOP reduction. 44,45 However, to our knowledge, no MIGS pivotal trials to-date have specifically explored outcomes with stratification by preoperative IOP and medications.…”
Section: Introductionmentioning
confidence: 99%